Total Phenolic, Anthocyanin, Catechins, DPPH Radical Scavenging Activity, and Toxicity of Lepisanthes alata (Blume) Leenh - Tuty Anggraini; Syafni Wilma; Daimon Syukri; Fauzan Azima (International Journal of Food Science)
Anthocyanins and catechin are natural antioxidants presented in many plants. Lepisanthes alata (Blume) Leenh is a plant with fruit that ripens to an intense red. This coloring suggests a high polyphenol content. However, limited information is available regarding the polyphenol or other antioxidant content in this fruit or its suitability as a food additive. The purpose of this research was to determine the total phenolic, total monomeric anthocyanin, catechin, epicatechin and epigallocatechin gallate content, DPPH radical scavenging activity, and toxicity in rind, flesh, seed, and whole fruit of L. alata. This research was conducted using an exploratory method with four analyses; samples from six parts of the plant were analyzed for polyphenols (rind, fruit pulp, seeds, whole fruit, bark, and leaves), four for anthocyanins (rind, fruit pulp, seeds, and whole fruit), and six parts of the plant for DPPH radical scavenging activity in water, methanol, and ethanol (rind, fruit pulp, seeds, whole fruit, bark, and leaves) and toxicity. This plant was found to contain high levels of polyphenol; the lowest level was measured in the flesh (0.64 mg GAE/g of DW) and the highest in the whole fruit (2.87 mg GAE/g of DW). The lowest anthocyanin content is found in the flesh and the highest in the rind with the respective average values of 672.27 mg/100 g FW and 1462.82 mg/100 g FW. Epicatechin is the major catechin in whole fruit and bark of L. alata. L. alata DPPH radical scavenging activity was in the range of 21.23 to 92.5% depending on the solvent, and the highest activity was recorded in bark in ethanol extract. No toxins were found in any part of the plant indicating that an extract from it could be safely used as a natural antioxidant supplement in processed foods to protect against free radicals.